2022
DOI: 10.3390/molecules27123946
|View full text |Cite
|
Sign up to set email alerts
|

Benzamides Substituted with Quinoline-Linked 1,2,4-Oxadiazole: Synthesis, Biological Activity and Toxicity to Zebrafish Embryo

Abstract: To develop new compounds with high activity, broad spectrum and low-toxicity, 17 benzamides substituted with quinoline-linked 1,2,4-oxadiazole were designed using the splicing principle of active substructures and were synthesized. The biological activities were evaluated against 10 fungi, indicating that some of the synthetic compounds showed excellent fungicidal activities. For example, at 50 mg/L, the inhibitory activity of 13p (3-Cl-4-Cl substituted, 86.1%) against Sclerotinia sclerotiorum was superior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Some of these fragments can be linked to tremendous recent literature, for example bit 388 corresponds to a 1,2,4-oxadiazole ring. 1,2,4-Oxadiazole-derivatives have been largely neglected by medicinal chemistry until 2005, but in the past 15 years, research has grown exponentially 113 and only in 2022 researchers reported cytotoxic, 114 fungicidal, 115 anti-inflammatory, 114 antiparasitary and antiproliferative 116 effects of 1,2,4-oxadiazole derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these fragments can be linked to tremendous recent literature, for example bit 388 corresponds to a 1,2,4-oxadiazole ring. 1,2,4-Oxadiazole-derivatives have been largely neglected by medicinal chemistry until 2005, but in the past 15 years, research has grown exponentially 113 and only in 2022 researchers reported cytotoxic, 114 fungicidal, 115 anti-inflammatory, 114 antiparasitary and antiproliferative 116 effects of 1,2,4-oxadiazole derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were obtained in the design of quinoline-linked 1,2,4-oxadiazoles, where the quinoline moiety of the target compounds originated from the fungicide quinoxyfen. 75 Among them, compounds 54 and 55 had the highest efficacy against S. sclerotiorum with the EC 50 values of 6.67 mg L −1 and 5.17 mg L −1 , respectively, surpassing that of the standard quinoxyfen. In addition, compound 55 demonstrated low effects on zebrafish embryos with an acute toxicity value of 19.42 mg L −1 .…”
Section: 24-oxadiazole Derivatives With Pesticidal Activitymentioning
confidence: 95%
“…76 In addition, compound 9 containing flexible aryl ether had an EC 50 of 5.17 mg/L against S. sclerotiorum. 77 This may imply that the introduction of the diaryl ether structure in this scaffold structure is more favorable to enhance the fungicidal activity of the compounds.…”
Section: ■ Fungicidal Activitymentioning
confidence: 99%